Balance of moisture reserves and methods of their efficient use in short crop rotations of the Steppe of Ukraine - Shevchenko, Sergey; Tsyliuryk, Oleksandr; Shevchenko, Mykhailo; Hulenko, Oleksandr; Derevenets-Shevchenko, Kateryna; Kokhan, Andriy (Ecological Questions, 2025)
Soil moisture availability is crucial for plant growth, directly influencing crop productivity. In the Northern Steppe of Ukraine, regardless of tillage systems, an unsaturated soil moisture class is formed, preventing full annual saturation of the 1.5-metre soil layer due to insufficient winter precipitation, lack of snow cover, and high wind activity. Precipitation moistens the soil only to 90–110 cm, creating a dry layer between stored winter moisture and deeper reserves at the wilting point. During spring-summer, plant roots struggle to reach deeper moisture, causing drought stress and yield loss. The highest spring moisture reserves in the 0–150 cm layer were observed under differentiated (chisel) and shallow mulch (disk) tillage, reaching 169.7 mm and 160.5 mm, exceeding ploughing by 17.9 mm (11.8%) and 8.7 mm (5.7%). Chisel tillage increased moisture accumulation by 91.0–179.0 m³/ha in winter due to better snow retention. Water consumption for yield formation was lowest under shallow mulch tillage (107.0–112.8 mm), highlighting its efficiency. Despite a slight yield reduction, it improved water use by 1.1–1.2 times. Fertilisation increased productivity by 5–13.6%, exceeding 14.0% under shallow mulch tillage, demonstrating its advantages in water-limited conditions.